Small heterodimer partner negatively regulates C-X-C motif chemokine ligand 2 in hepatocytes during liver inflammation. Issue 1 (December 2018) - Noh, Jung-Ran; Kim, Yong-Hoon; Kim, Don-Kyu; Hwang, Jung; Kim, Kyoung-Shim; Choi, Dong-Hee; Lee, Seon-Jin; Lee, Hee; Lee, Tae; Weng, Hong-Lei; Dooley, Steven; Choi, Hueng-Sik; et al.
Abstract Recently, we reported that orphan nuclear receptor small heterodimer partner (SHP) is involved in neutrophil recruitment through the regulation of C-X-C motif chemokine ligand 2 (CXCL2) expression in a concanavalin A (ConA)-induced hepatitis model. In the present study, we examined the mechanisms underlying CXCL2 regulation by SHP and the cell types involved in liver inflammation. To this end, eitherShp knockout (KO) or wild-type (WT) bone marrow cells were transferred into sublethally-irradiated WT (KO → WT or WT → WT) orShp KO (KO → KO or WT → KO) recipients, followed by intravenous injection of ConA (20–30 mg/kg) 8 weeks later. The KO recipient groups showed higher ConA-induced lethality than the WT recipient groups. Accordingly, plasma alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels, and inflammatory cytokine expressions were significantly higher in the KO recipients than in the WT recipients regardless of donor genotype. Massively increased hepatocyte death in KO recipients, as determined by H&E and TUNEL staining, was observed after ConA challenge. Bone marrow chimera experiments andin vitro chemotaxis assay also showed that SHP-deficient hepatocytes have an enhanced ability to recruit neutrophils to the injured liver.In vitro promoter assays showed that SHP is a negative regulator ofCxcl2 transcription by interfering with c-Jun binding to the AP-1 site within theCxcl2 promoter. Collectively, SHP regulatesCxcl2 transcription in hepatocytes, playing a pivotal role in the recruitment of neutrophils. SHP-targeting strategies may represent alternative approaches to control fulminant hepatitis.